A Quantitative Study of the Relationship between Project Performance and BIM Use on Commercial Construction Projects in the USA. Issue 1 (2nd January 2019) - Kelly, David; Ilozor, Benedict
ABSTRACT: This article reports the findings of a quantitative study on the relationship between various project performance outcomes and the use of Building Information Modeling (BIM), within the commercial construction industry. The literature review identified inconsistent results among prior qualitative and quantitative work concerning the relationships of key project performance measures and BIM use. Data on 13 variables from 93 completed construction projects were collected and examined through a causal comparative research design. Projects that used BIM (in design or construction) were not found to experience significant performance outcomes when controlling for the contribution of other independent variables and covariates at the 95% confidence level (CL). At the lower 90% CL, however, projects using BIM in construction experienced significantly higher levels of schedule growth than projects that did not use BIM in construction. Recommendations are made for training of construction management staff as a step to avoid unwanted schedule growth associated with BIM use during construction. This study is one of a very small group of rigorous quantitative analyses of BIM project performance outcomes conducted to date; additionally, it is the only study that has analyzed BIM in a multivariate context that controlled for the contribution of other project variables not directly related to BIM use.